Thyroid Metastasis in Whole-Body 18F-FDG PET/CT Restaging of Small Cell Lung Cancer. (January 2022) - Vogel, Jonas; Tenev, Alina; Solass, Wiebke; Schwenck, Johannes; Dittmann, Helmut
Abstract : Abstract: Incidental findings of thyroid lesions, some of which show increased FDG uptake, are common in whole-body FDG PET/CT imaging of oncological patients. As metastases to the thyroid are extremely rare, it is often a matter of debate, whether thyroid lesions should be considered as benign goiter or evaluated further. Here, we present the case of a 65-year-old woman with history of small cell lung cancer and multiple thyroid lesions, classified as benign nodular goiter. Because in restating using 18 F-FDG PET/CT these lesions showed an increased FDG uptake and growth progression, decision was made for fine-needle aspiration, which revealed small cell lung cancer metastasis 14 months after first tumor diagnosis.